1972
DOI: 10.1126/science.176.4032.295
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyhemoglobin Elevation after Exposure to Dichloromethane

Abstract: Inhalation of dichloromethane vapor in concentrations of 500 to 1000 parts per million for 1 to 2 hours promptly initiated the formation of significant quantities of carbon monoxide in human subjects. The evidence suggests that carbon monoxide may be a metabolite of dichloromethane and, that exposure to concentrations of dichloromethane below the industrial threshold limit values may result in the formation of carbon monoxide in amounts that exceed the allowable limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…The halflife of carbon monoxide is prolong.ed during exposure to methylene chloride a,s compared to ordinary exposure to carbon monoxide. This occurrence was pr,eviously pointed out by Stewart et al (7), and it has been comfirmed in the present study. The results show that the concentration of COHb in blood increases -during exposure to methylene chloride in inspiratory air.…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…The halflife of carbon monoxide is prolong.ed during exposure to methylene chloride a,s compared to ordinary exposure to carbon monoxide. This occurrence was pr,eviously pointed out by Stewart et al (7), and it has been comfirmed in the present study. The results show that the concentration of COHb in blood increases -during exposure to methylene chloride in inspiratory air.…”
Section: Methodssupporting
confidence: 70%
“…Stewart et al (7) showed that no increase in the level of urobilinog.en could be demonstrated in man exposed to methylene chloride. Thus there was no increased endogenous formation of carbon monoxide due to an enhanced meta,bolism of hemoglobin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stewart et al (18) maintained that exposure to methylene chloride in concentrations close to the threshold limit value may elevate the COHb concentration to more than 5 0/0. The detrimental effect of carbon monoxide on the human nervous system is a ,known fact.…”
mentioning
confidence: 99%
“…9 It is partly metabolized by the body to carbon monoxide and carbon dioxide. 7,8,10,11,12 Measurement of methylene chloride in blood or expired air, carbon monoxide in expired air, and carboxyhemoglobin in blood can be used to monitor the magnitude of exposure.…”
Section: Methylene Chloridementioning
confidence: 99%